2021
DOI: 10.1002/cptc.202100042
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Promoted Reversible Sulfide/Iodide Exchange in Fluoroalkyl Sulfides Enabled by Electron Donor‐Acceptor Complex Formation

Abstract: Catalyst-free visible-light-mediated exchange of two photoredox active groups, a 4-perfluoropyridinylthio group and an iodide group, attached to a fluorinated alkyl fragment is described. The reaction can be preparatively performed in both directions by appropriate choice of wavelength, solvent, and counterion. In the forward reaction, alkyl sulfide interacts with an iodide anion to give alkyl iodide and a thiolate anion, with the driving force provided by blue light (455 nm). In the backward process, fluorina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…Recently, we studied the EDA complex in SPyf‐containing ammonium salt with iodide counterion [30b] . X‐Ray diffraction indicated a presence of a weak binding between sulfur atom and iodide anion.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we studied the EDA complex in SPyf‐containing ammonium salt with iodide counterion [30b] . X‐Ray diffraction indicated a presence of a weak binding between sulfur atom and iodide anion.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 9 containing tetrafluoropyridine fragment (PyfS) constitute another class of reagents, which were successfully employed in photoredox reactions based on cleavage of the C−S bond [63–66] (Scheme 12). They are obtained by thiol‐ene addition to gem ‐difluorostyrenes catalyzed by 9‐phenylacrydine under irradiation [63] .…”
Section: Fluoroalkylation Of Heteroatom‐substituted Alkenesmentioning
confidence: 99%
“…The primary products were not isolated, but were converted into 3-fluorofurans upon brief treatment of the reaction mixture with acid. [61] Compounds 9 containing tetrafluoropyridine fragment (PyfS) constitute another class of reagents, which were successfully employed in photoredox reactions based on cleavage of the CÀ S bond [63][64][65][66] (Scheme 12). They are obtained by thiol-ene addition to gem-difluorostyrenes catalyzed by 9phenylacrydine under irradiation.…”
Section: Silyl Enol Ethersmentioning
confidence: 99%
“…[28][29][30][31] On the other hand, the desulfurization of the second class of thioethers (D or G) can be achieved by initial SET reduction of thioethers containing either tetra-fluoropyridine or thiazolium cores (Scheme 8B). [32][33][34][35][36][37][38][39][40] The splitting of the CÀ S bond in the radicals E or H then leads to the carbon radicals and either a stabilized thiolate F or the 3methylthiazolidine-2-thione J byproduct.…”
Section: Desulfurization Of Thioethersmentioning
confidence: 99%
“…The use of fluorinated PyfS derivatives was then investigated in the visible‐light promoted desulfurative iodination (Scheme 15). [36] It was found that reaction of difluorinated thiol precursors 48 with an excess of LiI in DMF at 5 °C under blue LED irradiation afforded the corresponding iodides 49 in high yields. Monofluorinated thiol precursors could be transformed under violet light, whereas no reaction was observed for fluorine‐free alkyl groups.…”
Section: Desulfurization Of Thioethersmentioning
confidence: 99%